1972
DOI: 10.1111/j.1151-2916.1972.tb11244.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Behavior and Microstructure of Vanadium Phosphate Glasses

Abstract: The magnetic properties and microstructures of the vanadium phosphate glass system over the composition range 60 to 90 m o % V,O, were investigated to study magnetic ordering in the glass and the effect of microstructure on its magnetic properties. Direct antiferromagnetic coupling between V" ions in the glassy matrix exists, and a transition temperature near -70°C was observed. As-cast glasses with high V,O, concentrations separated into two glassy phases; this separation increased the ESR line width as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…This type of behaviour of our films is consistent with that reported by other authors [27,28,30,39] that amorphous V20 s films exhibit a well-resolved hyperfine structure as compared to crystalline VzOs.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…This type of behaviour of our films is consistent with that reported by other authors [27,28,30,39] that amorphous V20 s films exhibit a well-resolved hyperfine structure as compared to crystalline VzOs.…”
Section: Resultssupporting
confidence: 94%
“…[261 studied the magnetic behaviour of xVzOs-{100-x)% AszO 3 glass and reported a change in the line width of ESR spectra due to coupling between V 3 +_V 4 + and V 4 + -V 4 § ions at different compositions. Friebele et al [27] and Nicula et al [26] suggested that the antiferromagnetic coupling between reduced vanadium ions (V 4+, V 3+, V 2+) in vanadate glasses reduces the concentration of V ~'+ ions. Friebele et al [27] further noted that as the concentration of V2Os in the vanadate glasses increases the concentration of V 4+ ions decreases.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some reduction of vanadium ions related to oxygen gas evolution during melting were observed. The reduced vanadium ratio (=c) increased with increasing P20~ content as indicated in other reports (29,30).…”
Section: Resultssupporting
confidence: 82%
“…This change in peak intensity is most likely related to the ratio of vanadium sites with 4+ and 5+ oxidation states; in several previous studies it was shown that the intensities of the two vanadium K-edge pre edge peaks in lithium vanadium phosphate glasses were consistent with the V 4+ and V 5+ fraction as determined independently using EPR studies. [49][50][51][52] The crystal structure of Ag 0.48 VOPO 4 has two similar vanadium sites that each have a silver ion in close proximity at a distance of ∼3.7 Å. Depending on whether this silver site is vacant, the neighboring vanadium ions may have initially have either a 4+ or 5+ oxidation state.…”
Section: Electrochemicalmentioning
confidence: 99%